UKRAINIAN CINEMATOGRAPHY IN THE CONTEXT OF STATE GOVERNANCE HISTORICAL DEVELOPMENT - Nadya, Lebyedyeva (Journal of Social, Humanity, and Education, 2022)
Purpose:  The main aim of the article is to cover the existing features of public administration of cinematography in historical dynamics and to reveal the presence of positive development. Research Methodology: The study used a general logical method of analyzing scientific sources of modern Ukrainian historians to assess the phenomena that have influenced the state of cinematography. The system of development of cinematography during the Soviet Union was taken into attention. Its influence on Ukrainian cinematography was analyzed. The regulatory documents on state support for cinematography from official sources were studied.  Results: Based on the documents' data a diagram showing the transition of the development of cinematography in Ukraine to a higher level was built. It entails new modeling of development in the future.  Limitations: This research uses the descriptive approach dew the special of the theme. Contributions: The novelty and significance of the worldwide humanitarian science lie in the fact that the demonstration of the general experience of Ukraine in the field of cinematography can be used by scientists from other countries to build appropriate management mechanisms in their countries.